(untitled) (Proceedings of International Conference on Modern Science and Scientific Studies, 2024)
This thesis describes the preparation of future informatics teachers for professional activity on the basis of organizational and pedagogical competencies. The content, form, tools and methods of developing organizational-pedagogical competencies in students have their own characteristics. In order to study these features, we turned to a number of scientific sources, scientific researches and developments within the framework of the dissertation work.